H-BN/graphene van der Waals vertical heterostructure: a fully spin-polarized photocurrent generator. Issue 1 (6th December 2017) - Tao, Xixi; Zhang, Lei; Zheng, Xiaohong; Hao, Hua; Wang, Xianlong; Song, Lingling; Zeng, Zhi; Guo, Hong
Abstract : A new scheme for generating perfect spin-polarized quantum transport in zigzag-edged graphene nanoribbons is demonstrated by light irradiation on a h -BN/graphene/ h -BN van der Waals (vdW) heterostructure. Abstract : By constructing transport junctions using graphene-based van der Waals (vdW) heterostructures in which a zigzag-edged graphene nanoribbon (ZGNR) is sandwiched between two hexagonal boron-nitride sheets, we computationally demonstrate a new scheme for generating perfect spin-polarized quantum transport in ZGNRs by light irradiation. The mechanism lies in the lift of spin degeneracy of ZGNR induced by the stagger potential it receives from the BN sheets and the subsequent possibility of single spin excitation of electrons from the valence band to the conduction band by properly tuning the photon energy. This scheme is rather robust in that we always achieve desirable results irrespective of whether we decrease or increase the interlayer distance by applying compressive or tensile strain vertically to the sheets or shift the BN sheets in-plane relative to the graphene nanoribbons. More importantly, this scheme overcomes the long-standing difficulties in traditional ways of using solely electrical field or chemical modification for obtaining half-metallic transport in ZGNRs and thus paves a more feasible way for their application in spintronics.